Thoughts on Aneuploidy - Torres, Eduardo M. (2011)
Aneuploidy refers to karyotypic abnormalities characterized by gain or loss of individual chromosomes. This condition is associated with disease and death in all organisms in which it has been studied. We have characterized the effects of aneuploidy on yeast and primary mouse cells and found aneuploidy to be detrimental at the cellular level. Furthermore, we find that aneuploid cells exhibit phenotypes consistent with increased energy need and proteotoxic stress. These observations together with the finding that the additional chromosomes found in aneuploid cells are active lead us to propose that aneuploidy causes an increased burden on protein synthesis and protein quality control pathways and so induces an aneuploidy stress response.